Effects of dietary zinc chloride hydroxide and zinc methionine on the immune system and blood profile of healthy adult horses and ponies. Issue 1 (2nd January 2023) - van Bömmel-Wegmann, Sarah; Zentek, Jürgen; Gehlen, Heidrun; Barton, Ann-Kristin; Paßlack, Nadine
ABSTRACT: The effects of dietary zinc on the immune function of equines have not been evaluated in detail so far. In the present study, eight healthy adult ponies and two healthy adult horses were fed a diet supplemented with either zinc chloride hydroxide or zinc methionine in six feeding periods of four weeks each (according to maintenance zinc requirement, 120 mg zinc/kg dry matter, and 240 mg zinc/kg dry matter, for both dietary zinc supplements, respectively). All animals received the six diets, with increasing amounts of zinc chloride hydroxide in the feeding periods 1–3, and with increasing amounts of zinc methionine in the feeding periods 4–6. At the end of each feeding period, blood samples were collected for a blood profile and the measurement of selected immune variables. Increasing dietary zinc chloride hydroxide doses increased the glutathione concentrations in the erythrocyte concentrate and the glutathione peroxidase activity in the erythrocyte lysate, decreased the numbers of total leukocytes and granulocytes in the blood, and also decreased the interleukin-2 concentrations in the plasma of the animals. The dietary supplementation of increasing doses of zinc methionine enhanced the mitogen-stimulated proliferative activity of peripheral blood mononuclear cells, and decreased the glutathione concentrations in the erythrocyte concentrate and the glutathione peroxidase activity in the plasma of the animals. The percentage of blood monocytes with oxidative burst after in vitro stimulation with E. coli decreased with increasing dietary zinc concentrations, independently of the zinc compound used. The blood profile demonstrated effects of the zinc supplements on the red blood cells and the bilirubin metabolism of the horses and ponies, which require further investigation. Overall, high doses of dietary zinc modulate the equine immune system, for the most part also depending on the zinc compound used.